Analysis of the Impact of Online Marketing Campaigns on Consumer Behavior in Indonesia's E-Commerce Market - Santosa, Handi Dipo; Manulang, Leo; Saputra, Ramadani; Sofiati, Evi (Universitas Negeri Makassar, 2024)
The rapid growth of e-commerce in Indonesia has transformed the way consumers interact with brands, largely influenced by the proliferation of online marketing campaigns. With the increasing use of digital platforms, businesses are leveraging targeted campaigns to influence consumer behavior, which plays a crucial role in purchasing decisions. This study aims to analyze the impact of online marketing campaigns on consumer behavior in Indonesia's e-commerce market, focusing on how elements such as personalization, promotions, and social media engagement shape consumer preferences and purchasing patterns. A quantitative research approach was employed, utilizing surveys distributed to 400 e-commerce users across major cities in Indonesia. The data was analyzed using statistical tools to determine the correlation between the effectiveness of marketing campaigns and changes in consumer behavior. The results indicate that personalized marketing campaigns, especially those delivered via social media platforms, have a significant positive effect on consumer engagement and purchase intent, with 68% of respondents more likely to complete a purchase following exposure to tailored promotions. Additionally, discounts and limited-time offers were found to be the most effective drivers of consumer action, contributing to increased sales and brand loyalty. However, the study also identifies challenges such as consumer skepticism towards overly aggressive marketing tactics, which may lead to decreased trust in the brand. Overall, this research provides valuable insights into the strategies that can enhance consumer engagement and purchasing behavior in Indonesia’s dynamic e-commerce market, offering practical recommendations for marketers to optimize their online campaigns.